Going Against the Grain: Gender-specific Media Education in Catholic High Schools - Lapayese, Yvette V. (Catholic Education: A Journal of Inquiry and Practice, 2012)
The Catholic Church has addressed the power of media, as well as the critical importance of understanding and educating Catholic youth on the media’s role and place in modern culture. In this article, the narratives of female Catholic teachers are prioritized to illustrate how gender-specific media education influences the schooling experiences of female high school youth. Eleven Catholic teachers participated in critical media literacy workshops to address the need to both understand and counter the powerful and often dangerous media messages targeted at girls. This is an exploratory study attempting to understand the possibilities of gender-specific education for our Catholic youth. A media literacy framework provides the lens through which the researcher analyzes the data and asserts that gender-specific media education provides a space for Catholic girls to engage in academic and faith-based acts of inquiry in innovative and relevant ways. As a result, gender-specific media education sets the stage for the development of female Catholic voices.